Teori Kebijakan Moneter - Adeliya Gita Silviana Putri; Della Nur Maulidya; Muhammad Irfan (CV. ITTC INDONESIA, 2024)
Monetary policy is an important instrument in controlling a country's economy. This journal discusses the concept and theory of monetary policy, strategies and mechanisms for monetary policy transmission through the path of quantity and price, as well as the effectiveness of monetary policy. The purpose of this research is to find out the concept and theory of monetary policy. The discussion includes the definition of monetary policy, the mechanism of monetary policy transmission: quantity and price, and the effectiveness of monetary policy. This study uses literature study methods from various sources, such as books, journals, and scientific articles, which discuss the concept and theory of monetary policy, monetary policy transmission strategies and mechanisms, and the effectiveness of monetary policy in Indonesia. This journal concludes that monetary policy in Indonesia is quite effective in maintaining price stability and the rupiah exchange rate, but it is still limited in encouraging economic growth.